2017
DOI: 10.1007/s00436-017-5413-2
|View full text |Cite
|
Sign up to set email alerts
|

Encystment of parasitic freshwater pearl mussel (Margaritifera margaritifera) larvae coincides with increased metabolic rate and haematocrit in juvenile brown trout (Salmo trutta)

Abstract: Gill parasites on fish are likely to negatively influence their host by inhibiting respiration, oxygen transport capacity and overall fitness. The glochidia larvae of the endangered freshwater pearl mussel (FPM, Margaritifera margaritifera (Linnaeus, 1758)) are obligate parasites on the gills of juvenile salmonid fish. We investigated the effects of FPM glochidia encystment on the metabolism and haematology of brown trout (Salmo trutta Linnaeus, 1758). Specifically, we measured whole-animal oxygen uptake rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
1
27
1
Order By: Relevance
“…It has been proposed earlier that the relationship between M. margaritifera glochidia and fish host is neutral or mutualistic (e.g., Ziuganov, ; Ziuganov et al., ), but our results provide evidence that the relationship at least moderately antagonistic. Therefore, our data is consistent with previous studies, which demonstrated that brown trout infected with freshwater pearl mussel glochidia perform generally worse compared to uninfected fish (Filipsson et al., ; Österling et al., ; Taeubert & Geist, ; Thomas et al., ). This is in line with the fact that freshwater pearl mussel glochidia grow intensively on the fish gills and obtain nutrients from their hosts (Denic et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It has been proposed earlier that the relationship between M. margaritifera glochidia and fish host is neutral or mutualistic (e.g., Ziuganov, ; Ziuganov et al., ), but our results provide evidence that the relationship at least moderately antagonistic. Therefore, our data is consistent with previous studies, which demonstrated that brown trout infected with freshwater pearl mussel glochidia perform generally worse compared to uninfected fish (Filipsson et al., ; Österling et al., ; Taeubert & Geist, ; Thomas et al., ). This is in line with the fact that freshwater pearl mussel glochidia grow intensively on the fish gills and obtain nutrients from their hosts (Denic et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…More importantly, D. pseudospathaceum along with many other trophically transmitted parasite species (see Poulin, 2010 for the review) are able to manipulate host behavior predisposing fish to predation by the definitive host-fish-eating bird (e.g., Crowden & Broom, 1980;Gopko et al, 2015Gopko et al, , 2017Mikheev et al, 2010;Seppälä et al, 2004Seppälä et al, , 2008. Therefore, by increasing the probability of concomitant infection freshwater pearl mussel glochidia can hamper their hosts in more subtle ways than it was suggested earlier (Filipsson et al, 2017;Österling et al, 2014;Thomas et al, 2014) which are not easy to detect without conducting comprehensive experimentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as a result of the early larval rejection, the parasitism was localized in clusters and below 300 glochidia/fish g, following the recommendations for artificial breeding of this naiad (Taeubert & Geist, ). Thus, the impaired respiratory function might be balanced and alleviated due to redistribution of blood flow to non‐affected gill regions (Booth, ) or other compensatory mechanisms (Filipsson et al, ; Powell, Nowak & Adams, ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of negative effects of M. margaritifera on its fish host have been described. M. margaritifera glochidia cause hyperplasia and fusion of gill filaments (Treasurer & Turnbull, 2000;Thomas et al, 2014), inhibit swimming capability and increase mortality (Taeubert & Geist, 2013), reduce foraging, activity and dominance success (Ö sterling et al, 2014;Filipsson et al, 2016), induce spleen enlargement and lessen mucous cells of gills (Thomas et al, 2014) and increase metabolic rate and level of hematocrit (Filipsson et al, 2017). Therefore, our hypothesis was that M. margaritifera glochidia infection is harmful, decreasing the growth of the fish host, brown trout.…”
Section: Introductionmentioning
confidence: 99%